Personalized Organoid-Based Treatments in Older Patients with Cancer: A Registry Study in Progress - Pirmin Häuptle; Kirsten Mertz; Michèle Voegeli; Robert Rosenberg; Emanuel Burri; Svetozar Subotic; Anna Romanens; Anne Leuppi-Taegtmeyer; Christian Regenbrecht; Lena Wedeken; Marcus Vetter (healthbook TIMES. Oncology Hematology)
The treatment of older patients with cancer is challenging owing to frailty and the presence of comorbidities, which complicate treatment decisions by impacting tolerance to therapeutic interventions, as well as poor representation of this patient population in clinical trials, leading to a lack of evidence-based data, especially in later lines of therapy. There is an urgent need for predictive models that could provide diagnostic and prognostic information relevant to older patients with cancer. Organoid technology has emerged as a promising frontier in cancer treatment, offering a versatile platform for personalized medicine and drug development. By recapitulating the three-dimensional (3D) architecture, cell-matrix interactions and tissue heterogeneity, organoid cultures provide an accurate representation of individual tumor properties, thus enabling the precise modeling of tumor behavior. Clinical trials have demonstrated a high predictive value and statistically significant correlation between the patient’s clinical response and tumor organoid response in different cancer types. The first ongoing Swiss registry study aims to apply organoid-based drug screening technology to identify optimal treatments in older cancer patients in the second or later therapy line setting. This study will help to identify optimal personalized treatment strategies while reducing unnecessary treatment-related toxicity and improving patient outcomes in this patient population.